The Geostrategic Importance of the Arctic: A Study of Cooperation and Competition: (Al-Mostansiriyah journal for Arab and international studies, 2026)
In addition to the geostrategic importance of the Arctic region, the climate changes that the region has witnessed have led to increased international interest through forms of cooperation or competition between many countries, including Russia, the United States of America, Canada, Norway, and Denmark, which competed over the demarcation of maritime borders and sovereignty over the continental shelf, while other countries from outside the region sought As is the case with China, which has sought to consolidate its presence in emerging Arctic diplomacy, alongside its growing military presence in the region, this has made the Arctic an arena for both competition and cooperation .Keywords: Arctic, geostrategic importance, areas of cooperation, major power competition